PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP KINERJA PEGAWAI PADA DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN KARAWANG - Aditya Batistuta Maulana; Cecep Hermana (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine the effect of competence and training on employee performance at the Manpower and Transmigration Office, Karawang regency. The research method used is descriptive verification with a quantitative approach. The research sample was 100 employees, using nonprobability sampling. The analysis used is path analysis and hypothesis testing using the t test and F test. The results of this study indicate that there is a correlation between competence and training of 0.864, which means that there is a strong relationship. The results of the partial hypothesis test Competence have a positive and significant effect on employee performance, training has a positive and significant effect on employee performance. The simultaneous hypothesis results of competence and training simultaneously have a significant effect on employee performance. R2 test for Competency and Training on Employee Performance obtained R Square of 0.923, meaning that 92.3% of employee performance is influenced by these two variables, while 7.9% of employee performance is influenced by other variables not examined in this study.